2022
DOI: 10.4235/agmr.22.0072
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Ability of the Three-Time Stand and Walk Test to Determine Frailty and its Associations with Fear of Falling and Cognitive Function in Community-Dwelling Older Adults

Abstract: Research protocols of the study were approved by the institutions' human research ethics committees (Ethics Committee reference number: 2/064/61).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Among all the tests, it was found that the TTSW had the highest predictive value, followed by the SLS, both of which had outstanding predictive abilities. The TTSW is very challenging and demanding for muscles in the lower extremities, and for assessing balance control and walking ability [ 16 ]. While the SLS is a test that reduces the base of support and appears to be a simple test, it is actually a very difficult task for older individuals who need to maintain posture in a stationary position on the narrow base of support for as long as they can.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among all the tests, it was found that the TTSW had the highest predictive value, followed by the SLS, both of which had outstanding predictive abilities. The TTSW is very challenging and demanding for muscles in the lower extremities, and for assessing balance control and walking ability [ 16 ]. While the SLS is a test that reduces the base of support and appears to be a simple test, it is actually a very difficult task for older individuals who need to maintain posture in a stationary position on the narrow base of support for as long as they can.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the TTSW we previously developed has excellent reliability (ICCs = 0.991; 95% CI = 0.984 to 0.996) [ 14 ]. The outcome of the test is used to indicate the risk of falling and frailty in older individuals [ 15 , 16 ]. Other balance tests, including FRT and SLS, have been reported to be useful for detecting balance impairment in the older individuals [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…1) Falls are a major public health issue in community-dwelling older adults, resulting in a lower quality of life and dependency. 2,3) In particular, impaired balance and sensory perception, leg muscle weakness, and decreased agility have been proposed as major risk factors for falls and increased fear of falling. [3][4][5] Previous research identified moder-been used to improve balance ability and reduce the rate of falling in older adults.…”
Section: Introductionmentioning
confidence: 99%